IMPLIKASI KRISIS EKONOMI AMERIKA SERIKAT TERHADAP EKSPOR KARET INDONESIA - Rizqi Apriani Putri; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The United States’s economy crisis because of housing subprime mortgage cause decrease of economy world 2008 that still continues until 2009. For the developed countries and emerging markets, this situation can damage economy fundamnetal and trigger economy crisis. the rubber cause becomes research object, first rubber becomes one of export commodity that gives chance to Indonesian for expanding the market. Second, rubber is the biggest donation from agriculture sector. Third, rubber is one of important farm commodity, both as income source, job chance and devisa, economy development for new centrals in surrounding and evironment and natural resources and as country with the biggest area and the second production in the world.The research methode that is used by the writer is the analyze descriptive methode. It is research methode that is used to describe sistematicaly a moment or problem that become study topic sistematicaly and rely on analyze against the events from consequence perspective and data arrangement. In the implemention, this methode limits not only in collecting and data arrangement, but analyze and interpretation against those datas.The United State’s economy crisis causes Indonesian’s rubber export. The rubber export value influences decrease in 2009, the rubber price in domestic and international also influences decrease. Not only price and value of rubber export but also rubber production of Indonesia. Also influences deecrease so taht it has impact against the worker in the factory which are fired and the farmers change livelihood in to the palm.Keywords: The United State’s Economy Crisis, Rubber, Subprime Mortgage